Trade in 'Virtual Carbon' : Empirical Results and Implications for Policy - Atkinson, Giles; Hamilton, Kirk; Ruta, Giovanni; Van Der Mensbrugghe, Dominique (World Bank, Washington, DC, 2014)
The fact that developing countries do not have carbon emission caps under the Kyoto Protocol has led to the current interest in high-income countries in border taxes on the "virtual" carbon content of imports. The authors use Global Trade Analysis Project data and input-output analysis to estimate the flows of virtual carbon implicit in domestic production technologies and the pattern of international trade. The results present striking evidence on the wide variation in the carbon-intensiveness of trade across countries, with major developing countries being large net exporters of virtual carbon. The analysis suggests that tax rates of $50 per ton of virtual carbon could lead to very substantial effective tariff rates on the exports of the most carbon-intensive developing nations.